Binegativity Exacerbates the Effects of Sexual Victimization Disclosure on Posttraumatic Stress and Drinking Among Bisexual Women - Salim, Selime R. (Journal of interpersonal violence, 2022)
Bisexual women experience higher rates of sexual victimization and mental health problems compared to heterosexual and lesbian women. Bisexual women also receive more unsupportive or overtly negative reactions when they disclose experiences of sexual victimization. The current study aimed to examine the interaction of negative social reactions and binegativity (i.e., experiences of stigma due to bisexual identity) in predicting posttraumatic stress, depression, and hazardous drinking among bisexual women. The sample consisted of 161 young adult bisexual women (ages 18?35) who disclosed a sexual victimization experience to at least one person. Moderation analyses were conducted via the PROCESS macro for SPSS. ?Turning against? reactions to disclosure (e.g., victim blame and avoidance of the victim) predicted increased posttraumatic stress and hazardous drinking in the presence of binegativity. In addition, reactions to disclosure that acknowledged the experience but were unsupportive predicted increased drinking in the context of binegativity. Depression was not associated with either type of negative reactions, regardless of binegativity. Thus, findings suggest that binegativity in combination with negative responses to disclosure of sexual victimization are important factors in specific types of distress related to sexual violence among bisexual women. Implications for research, clinical intervention, and policy are discussed.